2008
DOI: 10.1016/j.bbrc.2008.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between bax, reactive oxygen species production, and cardiolipin oxidation during apoptosis

Abstract: Bax/Bak activation and cardiolipin peroxidation are essential for cytochrome c release during apoptosis, yet, the link between them remains elusive. We report that sequence of events after exposure of mouse embryonic fibroblast (MEF) cells to actinomycin D followed the order: Bax translocation -> superoxide production -> cardiolipin peroxidation. Genetic ablation of Bax/Bak inhibited actinomycin D induced superoxide production and cardiolipin peroxidation. Rotenone caused robust superoxide generation but did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 28 publications
2
38
1
Order By: Relevance
“…Although T3-rich fraction was found to upregulate p53 expression in RKO cells (37), our results show that γ-T3 did not upregulate p53 expression but instead induced DR5 and DR4 in a p53-dependent manner. Bax is reported to play a role upstream of ROS production in neuron cells (50). However, at this time point, it is not clear how Bax is involved in the upregulation of DRs by γ-T3.…”
Section: Discussionmentioning
confidence: 88%
“…Although T3-rich fraction was found to upregulate p53 expression in RKO cells (37), our results show that γ-T3 did not upregulate p53 expression but instead induced DR5 and DR4 in a p53-dependent manner. Bax is reported to play a role upstream of ROS production in neuron cells (50). However, at this time point, it is not clear how Bax is involved in the upregulation of DRs by γ-T3.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, the fact that HeLa cells expressing the caspase non-cleavable p75 D255A mutant did not produce any ROS in response to TNFa/CHX confirms that complex I is one major source of this ROS generation. It has been reported that ROS can be a direct consequence of Bax/Bak-mediated MOMP (Kirkland et al, 2002;Kirkland and Franklin, 2003;Kirkland and Franklin, 2007;Jiang et al, 2008, Childs et al, 2008, because of the loss of cytochrome c from the respiratory chain complex III/IV and the fall in the mitochondrial membrane potential. This might be the case for apoptotic stimuli such as etoposide or tunicamycin, which did not provoke p75 cleavage despite effective cytochrome c release, and did not depend on p75 for ROS production and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a recent study using HEK 293, HeLa and cervix carcinoma cells reported that TNFainduced mitochondrial ROS production was mediated by the recruitment of the survival factor Bcl-x L to a mitochondrial protein called Romo1, which then resulted in a reduction of the mitochondrial membrane potential (Kim et al, 2010). Other studies claimed that MOMP itself triggered ROS production (Kirkland et al, 2002;Kirkland and Franklin, 2003;Kirkland and Franklin, 2007;Jiang et al, 2008). Finally, complex III of the respiratory chain was found to be involved in mitochondrial ROS formation induced by Bak in vascular endothelial cells (Childs et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…The amount of ROS does not necessarily correlate with the degree of oxidative damage ( 44 ). Therefore, oxidized products of biomolecules uniquely derived from a particular ROS may provide conclusive evidence to identify the responsible ROS.…”
Section: Reaction Mechanism For Dihydroperoxidesmentioning
confidence: 99%